International organizations and the promotion of effective dispute resolution : AIIB Yearbook of International Law 2019 - Quayle, Peter; Gao, Xuan (Lawyer) (AIIB yearbook of international law ;, 2019)
This second volume of the 'AIIB Yearbook of International Law' examines the role of international organizations in promoting effective dispute resolution. It is divided into five parts to reflect a series of overarching themes and relationships. Firstly, international arbitration's effectiveness and affinity with multilateral institutions. Second, international organizations as proponents of the norms of dispute resolution. Third, the dispute resolution mandates of international organizations. Fourth, the role of dispute resolution and economic development. The fifth part presents the 2018 AIIB Law Lecture and the 2018 AIIB Legal Conference Report. This diversity of perspectives offers convincing evidence that effective dispute resolution is a precondition to successful economic development - and that international organizations have an essential role to play in promoting both.